About Edom and Idumea in the Persian period: recent research and approaches from archaeology, Hebrew Bible studies and ancient Near Eastern studies - Hensel, Benedikt; Ben Zvi, Ehud; Edelman, Diana Vikander (Worlds of the ancient Near East and Mediterranean, 2022)
"This volume highlights and advances new developments in the study of Edom and Idumea in eighteen essays written by researchers from different disciplines"--